Interfaces of the Word : Studies in the Evolution of Consciousness and Culture - Ong, Walter J. (Book collections on Project MUSE., 1977)
In Interfaces of the World, Walter J. Ong explores the effects on consciousness of the word as it moves through oral to written to print and electronic culture.